Computed Tomography and Pathobiomechanical-Based Treatment of Volar Distal Radius Fractures - Hintringer, Wolfgang; Rosenauer, Rudolf; Quadlbauer, Stefan (Journal of Wrist Surgery, 2021)
Today, there are various classifications for distal radius fractures (DRF). However, they are primarily based on plain radiographs and do not provide sufficient information on the best treatment option. There are newer classifications that simultaneously consider the pathobiomechanical basis of the fracture mechanism and analysis of computed tomography images. Main determinants of which type of DRFs occurs are the strength/direction of the applied forces on the carpus and radius, and the position of the wrist relative to the radius during the fall. Reconstruction of the mechanism of injury provides information about which anatomic structures are involved, such as torn ligaments, bone fragments, and the dislocated osteoligamentous units. This article attempts to combine and modify current pathobiomechanically oriented classifications with an improved understanding of the “key fragments” to subsequently offer a treatment approach to stabilize these critical fragments through specific types of internal fixation.
Keywords: distal radius fracture; volar locking plate; complications; outcome; radiological